Coping With Metal Toxicity – Cues From Halophytes - Nikalje, Ganesh C.; Suprasanna, Penna (Frontiers in Plant Science, 2018)
Being the native flora of saline soil, halophytes are well studied for their salt tolerance and adaptation mechanism at the physiological, biochemical, molecular and metabolomic levels. However, these saline habitats are getting contaminated due to various anthropogenic activities like urban waste, agricultural runoff, mining, industrial waste that are rich in toxic metals and metalloids. These toxic metals impose detrimental effects on growth and development of most plant species. Halophytes by virtue of their tolerance to salinity also show high tolerance to heavy metals which is attributed to the enhanced root to shoot metal translocation and bioavailability. Halophytes rapidly uptake toxic ions from the root and transport them toward aerial parts by using different transporters which are involved in metal tolerance and homeostasis. A number of defense related physiological and biochemical strategies are known to be crucial for metal detoxification in halophytes however; there is paucity of information on the molecular regulators. Understanding of the phenomenon of cross-tolerance of salinity with other abiotic stresses in halophytes could very well boost their potential use in phytoremediation. In this article, we present an overview of heavy metal tolerance in case of halophytes, associated mechanisms and cross-tolerance of salinity with other abiotic stresses.